NUP214 fusion genes in acute leukemias: genetic characterization of rare cases - Brunetti, Marta; Andersen, Kristin; Spetalen, Signe; Lenartova, Andrea; Osnes, Liv Toril Nygård; Vålerhaugen, Helen; Heim, Sverre; Micci, Francesca (Frontiers in Oncology, 2024)
Introduction Alterations of the NUP214 gene (9q34) are recurrent in acute leukemias. Rearrangements of chromosomal band 9q34 targeting this locus can be karyotypically distinct, for example t(6;9)(p22;q34)/DEK::NUP214, or cryptic, in which case no visible change of 9q34 is seen by chromosome banding. Methods We examined 9 cases of acute leukemia with NUP214 rearrangement by array Comparative Genomic Hybridization (aCGH), reverse-transcription polymerase chain reaction (RT-PCR), and cycle sequencing/Sanger sequencing to detect which fusion genes had been generated. Results The chimeras DEK::NUP214, SET::NUP214, and NUP214::ABL1 were found, only the first of which can be readily detected by karyotyping. Discussion The identification of a specific NUP214 rearrangement is fundamental in the management of these patients, i.e., AMLs with DEK::NUP214 are classified as an adverse risk group and might be considered for allogenic transplant. Genome- and/or transcriptome-based next generation sequencing (NGS) techniques can be used to screen for these fusions, but we hereby present an alternative, step-wise procedure to detect these rearrangements.